1970
DOI: 10.1079/bjn19700071
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of salts of volatile fatty acids by growing sheep

Abstract: I . An experiment is reported in which groups of six lambs were fed two basal diets supplemented at three levels with a mixture of sodium and calcium acetates.2. The basal diets were given in amounts that provided equal intakes of digestible organic matter and crude protein. One contained 85 % of concentrates (Hc), the other 40% of concentrates (Lc). Rumen contents from a sheep receiving diet Hc contained a lower molar proportion of acetate and higher proportions of propionate and butyrate than when diet Lc wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Lee-Rangel et al (2012) reported that inclusion of calcium propionate in the diets of lambs had no effect on their feed conversion. These observations suggest that the ME supplied by VFA is more efficiently utilized than the same amount of ME supplied by the diet (Poole and Allen, 1970). Inclusion of sodium propionate in diets increased (P = 0.01) weaning age in the current study.…”
Section: Effects Of Pro On Performancesupporting
confidence: 54%
“…Lee-Rangel et al (2012) reported that inclusion of calcium propionate in the diets of lambs had no effect on their feed conversion. These observations suggest that the ME supplied by VFA is more efficiently utilized than the same amount of ME supplied by the diet (Poole and Allen, 1970). Inclusion of sodium propionate in diets increased (P = 0.01) weaning age in the current study.…”
Section: Effects Of Pro On Performancesupporting
confidence: 54%
“…In contrast, lean offspring remained at pasture and had unrestricted physical activity. It is possible that differences in the amount of roughage consumed between pasture and barn-reared animals may have contributed to differences in the ratio of volatile fatty acid production (Poole and Allen 1970). Any such effects in the present study did not appear to have a major effect on glucose homeostasis, because this was comparable between all groups of animals when they were maintained on the same diet ).…”
Section: Resultsmentioning
confidence: 61%